Analysis of inter-decade changes in trends and spatial patterns of annual and seasonal precipitation, case study: West of Iran - Fatemeh Ghiasabadi Farahani; Faramarz khoshakhlagh; Aliakbar Shamsipour; Ghasem Azizi; ebrahim fattahi (تحقیقات کاربردی علوم جغرافیایی)
The present research about the spatial changes of precipitation is mainly focused on western areas of Iran. Precipitation data for three seasons of fall, winter, and spring have been obtained from Esafzari Database, with 15*15 km spatial resolution in the form of a Lambert Cone Image System for the period from 1986 to 2015. To examine the prevailing pattern of precipitation in west of Iran, we have used geostatistical methods of spatial autocorrelation. The changes in precipitation trends have been analyzed using parametric and non-parametric analyses of regression and Mann Kendal. We have used MATLAB for analysis of the data. We have also used ArcGIS and Surfer for drawing maps.  The results of inter-decade changes of positive spatial autocorrelation of precipitation in west of Iran have indicated that there has been a decline in spatial extent of the positive spatial autocorrelation pattern in spring and fall, except for winter with a negligible increasing trend. Nevertheless, except for the second period, no considerable spatial changes were observed in the spatial pattern of precipitation in the region. However, there was a decreasing trend in the negative spatial autocorrelation of precipitation in annual and seasonal scales. The results of trend analysis have indicated that there was a decreasing trend in a vast area of the west parts of the country in annual scale and also in winter. Although there was an increasing trend in precipitation in fall and spring, but the trend was not significant in 95 % of confidence interval. The results of Man Kendal test have confirmed the results obtained from linear regression.